J-shaped catheter for endobronchial aspiration of right upper lobe bronchus during rigid bronchoscopy in pediatric patients. - Majid, A.A. (1991)
A J-shaped suction catheter was tailored to facilitate aspiration of the right upper lobe bronchus during rigid bronchoscopy in pediatric patients. This suction catheter was used successfully in three patients.